2018
DOI: 10.1080/19312458.2018.1479843
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with Algorithms: A Transfer Entropy Analysis of Emotions-based Escapes from Online Echo Chambers

Abstract: Online algorithms have received much blame for polarizing emotions during the 2016 U.S. Presidential election. We use transfer entropy to measure directed information flows from human emotions to YouTube's video recommendation engine, and back, from recommended videos to users' emotions. We find that algorithmic recommendations communicate a statistically significant amount of positive and negative affect to humans. Joy is prevalent in emotional polarization, while sadness and fear play significant roles in em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 49 publications
0
27
0
2
Order By: Relevance
“…Although it can be methodologically convenient to separate studies into the ways that humans shape machines and vice versa, most AI systems function in domains where they co-exist with humans in complex hybrid systems 39,67,125,128 . Questions of importance to the study of these systems include those that examine the behaviours that characterize human-machine interactions including cooperation, competition and coordination-for example, how human biases combine with AI to alter human emotions or beliefs 14,55,56,129,130 , how human tendencies couple with algorithms to facilitate the spread of information 55 , how traffic patterns can be altered in streets populated by large numbers of both driverless and human-driven cars and how trading patterns can be altered by interactions between humans and algorithmic trading agents 29 as well as which factors can facilitate trust and cooperation between humans and machines 88,131 .…”
Section: Human-machine Co-behaviourmentioning
confidence: 99%
“…Although it can be methodologically convenient to separate studies into the ways that humans shape machines and vice versa, most AI systems function in domains where they co-exist with humans in complex hybrid systems 39,67,125,128 . Questions of importance to the study of these systems include those that examine the behaviours that characterize human-machine interactions including cooperation, competition and coordination-for example, how human biases combine with AI to alter human emotions or beliefs 14,55,56,129,130 , how human tendencies couple with algorithms to facilitate the spread of information 55 , how traffic patterns can be altered in streets populated by large numbers of both driverless and human-driven cars and how trading patterns can be altered by interactions between humans and algorithmic trading agents 29 as well as which factors can facilitate trust and cooperation between humans and machines 88,131 .…”
Section: Human-machine Co-behaviourmentioning
confidence: 99%
“…Similar symptoms also occurred among Twitter The 10th IGSSCI users in the momentum of the Presidential Elections in the United States in 2016 whichshowed a level of significant political homogeneity and opinion leadership which created homogeneous communities(Guo, Rohde, and Wu 2018). In this political event, it can also be seen how YouTube users have also experienced a split, namely the feeling of joy in relation to emotional variation and sadness and fear to play important roles in emotional convergence(Hilbert, Ahmed, Cho, Liu, and Luu 2018). This shows, again, that social media plays a more important role in emphasizing emotional strength than rational power in decisive political momentum.…”
mentioning
confidence: 68%
“…It is also important to start watching the video, as we found that YouTube's recommendation algorithm works on basis of the watch history, not on basis of the search history. We speculate that the reason is that the final consumption of online content is a mix of own search results and of input from their online friends (Gottfried & Shearer, 2016;Hilbert, Ahmed, Cho, Liu, & Luu, 2018).…”
Section: Data and Proceduresmentioning
confidence: 99%
“…Such interpretive power has given rise to omnipresent online recommender algorithms, which have become crucial gatekeepers in the management of today's communication landscape (Ricci, Rokach, Shapira, & Kantor, 2011). Their critical role has then again received much blame recently for creating filter bubbles and echo chambers that clearly restructure our communicational landscape (Bakshy, Messing, & Adamic, 2015;Colleoni, Rozza, & Arvidsson, 2014;Hilbert, Ahmed, Cho, Liu, & Luu, 2018;Pariser, 2011).…”
mentioning
confidence: 99%